GE_GERICHTE C/21927/2015 vom 10. April 2017 - GE Cour de justice (2017)
BAIL À FERME ; CONTESTATION DU CONGÉ ; DÉFAUT DE PAIEMENT ; FORMULE OFFICIELLE ; COMPENSATION DE CRÉANCES | CO.282; OBLF.9; CO.298;